THE EVOLVING LANDSCAPE OF PADDY CULTIVATION IN KERALA (International Journal of Food and Nutritional Sciences, 2021)
This study explores the evolving landscape of paddy cultivation in Kerala, focusing on thesocioeconomic, technological, and environmental changes that have shaped this sector. The studybased on both secondary and primary data sources, investigates the role of collective farminginitiatives such as Padashekhara Samithies and Joint Liability Groups (JLGs) of Kudumbashree inaddressing challenges like labour shortages, climate change, and technological changes. The studyalso examines the shift towards commercial crops, technology adoption in terms of the use of HighYielding Varieties seeds (HYVs) and implications for food security and sustainability. The studyobserves that despite the support from initiatives like Padashekhara Samithies and JLGs ofNeighbourhood Groups (NHGs), paddy cultivation in Kerala faces labour shortages, climaticuncertainties, and declining profitability, emphasizing the need for sustainable and climate-resilientpractices, conservation of traditional paddy varieties, and adoption of modern machinery. Futureresearch, therefore, should focus on developing innovative solutions to labour shortages, enhancingclimate-resilient practices, and promoting the conservation and use of traditional paddy varieties toensure the sustainability of paddy cultivation in Kerala.